1996
DOI: 10.1046/j.1365-2249.1996.d01-726.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tumour necrosis factor-alpha (TNF-α) mRNA and protein in pathological thyroid tissue and carcinoma cell lines

Abstract: There has been much controversy about the presence of TNF‐α within thyroid tissue. We therefore conducted a study to determine if TNF‐α mRNA is present in thyroid tissue and thyroid‐derived cells. Semiquantitative reverse transcriptase‐polymerase chain reaction (RT‐PCR) was employed with a heterologous competitor fragment. Significantly lower levels of TNF‐α mRNA were found in the autonomous nodules from patients with thyroid autonomy (TA; n = 4; 5.7 ± 1.3 arbitrary units (AU) (mean ± s.e.m.); P < 0.03) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 38 publications
(48 reference statements)
3
52
0
2
Order By: Relevance
“…This cytokine is detectable in thyroid tissues obtained from patients with Hashimoto's thyroiditis (Ajjan et al 1996, Aust et al 1996. In accordance, we and others have demonstrated enhanced TNF gene expression in the inflamed thyroid of BioBreeding/Worcester (BB/W) rats (Mori et al 1998, Bluher et al 1999.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…This cytokine is detectable in thyroid tissues obtained from patients with Hashimoto's thyroiditis (Ajjan et al 1996, Aust et al 1996. In accordance, we and others have demonstrated enhanced TNF gene expression in the inflamed thyroid of BioBreeding/Worcester (BB/W) rats (Mori et al 1998, Bluher et al 1999.…”
Section: Introductionsupporting
confidence: 87%
“…While the majority of TNF detected in inflamed thyroid tissues is produced by infiltrating inflammatory cells (Aust et al 1996), studies demonstrate the production of TNF by thyroid epithelial cells (Zheng et al 1992, Mori et al 1998. It may be possible that TNF produced by infiltrating inflammatory cells induces its own expression in thyrocytes in the area of infiltration, since autoinduction of TNF has been demonstrated in HL-60 human promyelocytic leukemia cells and in rat tracheal epithelial cells (Spriggs et al 1990, Bader & Nettesheim 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The oncogenes activated in thyroid carcinomas, including RET/PTC, RAS and BRAF, which trigger the MAPK cascade, can induce a cell-autonomous proinflammatory transcriptional program in thyrocytes, which includes expression of cytokines, chemokines and their receptors (7). Proinflammatory cytokines, such as tumor necrosis factor (TNF)-α and interferon (IFN)-γ, are important inflammatory mediators of these processes (8,9). TNF-α and IFN-γ are pleiotropic cytokines expressed in various types of tumor cells and cells in the tumor microenvironment, exerting a variety of pro-tumoral activities in solid tumors (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, tumor tissue or tumor-derived cell lines from differentiated carcinomas secrete G-CSF, GM-CSF, IL-1a, IL-6, IL-8, MCP-1 and/or TNF-a (Tohyama et al, 1992;Kayser et al, 1995Kayser et al, , 1996Nakada et al, 1996;Basolo et al, 1998;Kurebayashi et al, 2000;Scarpino et al, 2000), whereas undifferentiated thyroid carcinomas have been shown to produce the cytokines GROa, G-CSF, GM-CSF and IL-1a, IL-6, IL-8 and/or TNF-a (Enomoto et al, 1990;Yoshida et al, 1992Yoshida et al, , 1994Aust et al, 1996Aust et al, , 2001Basolo et al, 1998;Asakawa and Kobayashi, 1999). Moreover, the cell lines known to express an activated form of c-RET express the cytokines IL-6 and IL-8, suggesting that c-RET activation may directly signal cytokine expression (Basolo et al, 2002;Iwahashi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%